Correction: A systematic review of exercise testing in patients with intermittent claudication: A focus on test standardisation and reporting quality in randomised controlled trials of exercise interventions. - Stefan T Birkett; Amy E Harwood; Edward Caldow; Saïd Ibeggazene; Lee Ingle; Sean Pymer (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0249277.].